Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question is to find $x\in\left(0,\frac{\pi}{2}\right)$:

$$\frac {\sqrt3 - 1}{\sin x} + \frac {\sqrt3 + 1}{\cos x} = 4\sqrt2 $$

What I did was to take the $\cos x$ fraction to the right and try to simplify ;

But it looked very messy and trying to write $\sin x$ in terms of $\cos x$ didn't help.

Is there a more simple (elegant) way to do this.

share|cite|improve this question
divide both sides by $2\sqrt{2}$ and use the fact that $\sin(\frac{\pi}{6}) = \frac{\sqrt{3}-1}{2\sqrt{2}}$ and $\cos(\frac{\pi}{6}) = \frac{\sqrt{3}+1}{2\sqrt{2}}$ – dezdichado Mar 20 at 8:56
$\sin \frac \pi6$ is $\frac 12$, did you mean $\frac \pi{12}$? – user26977 Mar 20 at 8:59
up vote 7 down vote accepted

$\sin(\frac{\pi}{12}) = \frac{\sqrt{3}-1}{2\sqrt{2}}$ and $\cos(\frac{\pi}{12}) = \frac{\sqrt{3}+1}{2\sqrt{2}}$. Plugging them into your equation yields $\sin(x+\frac{\pi}{12}) = \sin(2x)$. So $x = \frac{\pi}{12}$

share|cite|improve this answer
It $\pi/12$ not $\pi/6$ – lab bhattacharjee Mar 20 at 9:00
yes edited accordingly – dezdichado Mar 20 at 9:01
Thanks for the answer – user307178 Mar 20 at 9:09

Another approach is to write the equation as

$(\sqrt{3} - 1) \cos x +(\sqrt{3} + 1) \sin x = 4 \sqrt2 \sin x \cos x$

then rearranging gives

$\frac{\sqrt{3} - 1}{2 \sqrt{2}} \cos x +\frac{\sqrt{3} + 1}{2 \sqrt{2}} \sin x = 2 \sin x \cos x$.

Now note that $(\frac{\sqrt{3} - 1}{2 \sqrt{2}})^2 +(\frac{\sqrt{3} + 1}{2 \sqrt{2}})^2 = \frac{1}{8} ((3 -2 \sqrt{3} + 1) + (3 +2 \sqrt{3} + 1) = 1$ so that we can write $\frac{\sqrt{3} - 1}{2 \sqrt{2}}$ as the $\sin$ of some angle, say $\alpha$, and identify $\frac{\sqrt{3} + 1}{2 \sqrt{2}}$ as $\cos \alpha$.

Then you have to solve $\sin(\alpha + x) = \sin(2x)$, with $\tan \alpha = \frac{\sqrt{3} - 1}{\sqrt{3} + 1}$.

share|cite|improve this answer

Replace $\sqrt3=\tan60^\circ,1=\tan45^\circ$

to find $$\sin(15^\circ+x)=2\sin x\cos x=\sin2x$$

Now if $\sin y=\sin A, y=n180^\circ+(-1)^nA$ where $n$ is any integer

As $\sqrt3-1=\tan60^\circ-\tan45^\circ=\dfrac{\sin(60-45)^\circ}{\cos60^\circ\cos45^\circ}=2\sqrt2\sin15^\circ$

Similarly, $\sqrt3+1=2\sqrt2\sin75^\circ=2\sqrt2\cos15^\circ$

share|cite|improve this answer
@user307178, Please follow the last two lines – lab bhattacharjee Mar 20 at 9:05
Thanks got it...My reputation is less so I can't upvote – user307178 Mar 20 at 9:07
@user307178, I actually tried to derive the sine/cosine value of $$\dfrac{\sqrt3\pm1}{2\sqrt2}$$ without assuming them. – lab bhattacharjee Mar 20 at 9:15
And I have learned a useful method to derive them! Because I always forget it. Thanks! – user307178 Mar 20 at 9:25
Do you know a similar trick to get sin18°? That would be awesome – user307178 Mar 20 at 9:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.